Analisis Kausalitas Kebebasan Sipil dan Pertumbuhan Ekonomi di Indonesia - Zainuddin; Muhammad Bakri; Muhammad Farras Mufadhdhal (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this analysis is to examine the causal relationship between civil liberties and economic growth in Indonesia. The data used are panel data from 34 provinces in Indonesia from 2021 to 2019, and the analysis tool after testing the selection of suitable analytical models to use in this analysis is the common effects model. The results of this analysis show that while civil liberties are positively important to Indonesia's economic growth, economic growth is not important to Indonesian civil liberties. Civil liberties capacity can affect economic growth by 0.17%, the rest is influenced by other variables not included in this analysis.